(untitled) (Research, Society and Development, 2021)
This article aims to describe the creation and development of a health educational video prepared on a digital platform in order to contribute to health education on gastrostomy. Considering that health education is knowledge intended for human development, the educational video is characterized as a support product with didactic purposes in the mediation of the teaching and learning process in different educational contexts. Six platforms were evaluated, Moravi, Promo-Brazil, Animoto.com, Sparkol, Doodly.com and VideoScrib. We selected the VideoScribe platform to execute the project. We hope that this product will add to health education on the subject, contributing to improving the quality of life of patients.